DIE CHRISTOLOGIESE UITLEG VAN DIE OU TESTAMENT EN DIE IMPLIKASIES VIR DIE PREDIKING - Spangenberg, Izak J. J. (Scriptura, 1985)
The Christological interpretation of the Old Testament in the preaching processThe idea that the Old Testament contains direct prophecies pertaining to Jesus Christ and that these prophecies, in some way or other, foreshadow Him, is still present in some circles. Such a notion can no longer be subscribed to. An analysis of Psalms 2, 8 and 22, and the way in which the New Testament authors utilized them, demonstrates this. This paper contends that not one of these Psalms represent a direct prophecy concerning the coming, passion, a crucifixion or resurrection of Jesus Christ. The New Testament authors utilized the Psalms to proclaim Jesus as the Christ of the Old Testament. This is of course something quite different that saying that the Psalms witness prophetically to Jesus.